Caracterização física e química de substratos com lodo de esgoto na produção de mudas de Aegiphila sellowiana Cham - Santos, Fernando Elair Vieira (2013)
The seedling production quality is associated among other factors, the characteristics and formulations of each substrate. Starting from this idea, the recent study had by appointment testing the efficiency of various wastes and vermiculite as a component and nutrients source for the substrates to the production of Aegiphila sellowiana plants looking for decrease the environmental Impact caused by the excess of these ones and connect the physical and chemical points from the substrates formulated with the quality of the produced plants. The substrates were formulated with different ratios of sewage sludge (80, 60, 40 and 20%) associated with coconut fiber, vermiculite, straw coffee fresh, organic compost (manure + straw in nature coffee), bark carbonized rice husk and rice fresh addition of a substrate with 100% sewage sludge and a control with 100% commercial substrate. The experiment was conducted in a completely randomized design with 26 treatments and five replications of four plants. Analyses of physical and chemical substrates formulated and pure components. Within 45 days after the implantation of the experiment was carried out thinning the seedlings, leaving only one individual per pot. Within 120 days after thinning the plants, was studied the variables of growing and indexes of quality. The use of different proportions of waste contributed to the some improvement of physical properties of the substrate. The increase in the proportion of sewage sludge led to a decrease of the macroporosity (Macrop), increased global density (Dg), easily available water (AFD), available water (AD) and microporosity (Microp) substrates formulated. Regarding the chemical analysis the commercial substrate has allowed the biggest averages for the available contents of the substrates. The sewer Iodine has allowed the increasing of fertility from the substrates with increasing of contents from nutrients mostly nitrogen and phosphorus and also the total content of soluble salts. The sewage sludge has allowed the increasing of fertility from the substrates with increasing of contents from nutrients mostly nitrogen and phosphorus and also the total content of soluble salts. According to the presented particularities, were considered more adequate chemically for the plants development from forest species the formulated substrates with the organic compost. The seedlings with higher proportions of sewage sludge resulted in higher means for height and stem diameter. The formulated treatments with organic compost especially with 60 and 80 % proportions, has allowed bigger averages for the morphometric characteristics assessed being the most suitable for the production of seedlings Aegiphila sellowiana. The commercial substrate provided the lowest averages for the morphometric characteristics evaluated. The highest accumulation of the aerial part of the seedlings Aegiphila sellowiana were obtained in the treatment with 40% sewage sludge associated with 60% of organic compost. Nutrients accumulated in the following descending order: macronutrients N> Ca> K> P> Mg> S